The expanded immunoregulatory protease network in mosquitoes is governed by gene coexpression - Bianca Morejon; Kristin Michel (Proceedings of the National Academy of Sciences, 2025)
Serine protease cascades regulate key innate immune responses. Their activation cleaves a series of inactive protease zymogens, which then activate downstream effector enzymes, ensuring a rapid response. In mosquitoes, these cascades involve clip-domain serine proteases and their noncatalytic homologs (CLIPs), whose make-up and structural organization are not fully understood. Here, we systematically assessed the contribution of individual CLIPs to humoral immunity in Anopheles gambiae , by performing gene knockdown of 85 of the 110 CLIPs in adult females and assessing their individual contribution to humoral immunity regulation. By coupling RNAi with assays measuring antimicrobial activity and melanization, we identified 27 immunoregulatory CLIPs. Only one CLIP contributed to both immune responses, thus providing evidence for largely distinct protease subnetworks controlling melanization and antimicrobial activity. CLIPs regulating antimicrobial activity were found to contribute to antimicrobial peptide expression and to control infection resistance, as knockdowns reduced bacterial load and improved survival. Furthermore, our analysis of CLIP gene expression unveiled a immunoregulatory mechanism reliant on protease baseline coexpression rather than infection-induced upregulation. Together, results from this study improve our understanding of immune system regulation by proteolysis and identify a layer of regulation that could be manipulated for mosquito control purposes.